Evaluating the Preventive and Therapeutic Roles of Active Irrigation Systems in Root Canal Treatment: A Narrative Review and Critical Appraisal of Theory and Methodology - Ignacio Barbero-Navarro; Iuliana Sofian-Pauliuc; Maria Esther Irigoyen-Camacho; Marco Antonio Zepeda-Zepeda; David Ribas-Perez; Antonio Luis Castaño-Seiquer (Dentistry Journal)
Endodontic therapy aims at preventing or curing apical periodontitis. To conduct this, the cleaning and shaping of the canals are essential. By using an irrigant, such as sodium hypochlorite (NaOCl), practitioners attempt to wash out debris, dissolve organic and inorganic tissue, lubricate the canals, prevent smear layer formation, and disrupt biofilms. Different methods have been developed to optimise the effectiveness of irrigants, including manual or passive techniques (the conventional method used worldwide) and active techniques (the irrigant is activated by certain devices to improve its flow in the root canal system). Some techniques included in the active category are ultrasonic and sonic methods, apical negative pressure irrigation, and multisonic activation. These active techniques appear to have higher effectiveness when compared to the conventional syringe method during the root canal treatment procedure. However, it is unclear whether they also have a higher influence on the treatment outcome and healing of apical periodontitis. There is a consensus on the need for endodontic studies with standardized protocols and methods to reach a standardized clinical protocol when using active irrigation.